Pengukuran Kinerja Rantai Pasokan Material Mobiya untuk Mendukung Proyek Khusus UNHCR - Devano, Alrido Martha; Tarigan, Yulinda; Naibahoa, Devi Masniar (Journal of Applied Business Administration, 2023)
The assessment of supply chain performance enables the monitoring of progress in supply chain management (SCM) and serves as a metric for assessing success in maintaining a competitive advantage The objective of this study is to ascertain the configuration of the supply chain flow and evaluate the performance of the material's supply chain at PT SCH, a company operating in the electrical industry. The employed methodologies encompass the Supply Chain Operations Reference (SCOR) and the Analytical Hierarchy Process (AHP), facilitated by the utilization of the Expert Choice 11 software. The supply chain movement at PT SCH encompasses three primary distribution networks, namely inbound, internal, and outbound. The Supply Chain Operations Reference (SCOR) model implemented at PT SCH has three tiers, including five core processes (plan, sourcing, making, delivering, and returning), three performance attributes (reliability, responsiveness, and flexibility), and a total of 19 performance indicators that have been customized to align with the specific requirements of the organization. Upon conducting performance measurements, a score of 75.70 out of 100.00 was obtained, categorizing it as "good."